Fe-based amorphous alloy capable of being industrially applied to degradation of high-COD (Chemical Oxygen Demand)-value wastewater as well as preparation method and application of Fe-based amorphous alloy
By combining Fe-based amorphous alloys with ozone, the treatment problem of high COD wastewater was solved. This method achieves efficient catalytic degradation under acidic to neutral conditions, improves the biodegradability of wastewater and catalyst lifespan, and is suitable for large-scale treatment of wastewater with different COD concentrations.
Patent Information
- Application Number
- CN202510951864.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-11-21
AI Technical Summary
Existing iron-based amorphous alloys require H2O2 as an oxidant when treating high COD wastewater. H2O2 is easily decomposed, has poor safety, and is not suitable for the water quality conditions of high COD wastewater, affecting the service life of the catalyst. Furthermore, existing ozone treatment is not effective and is difficult to degrade high COD wastewater, leading to a burden on subsequent biological treatment.
Using an Fe-based amorphous alloy with the chemical composition FeaCobNicMndSieBf as a catalyst, it is combined with ozone for catalytic degradation, avoiding mechanical stirring. It is suitable for acidic to neutral environments and is prepared through vacuum arc melting, high-vacuum single-roller quenching and spray casting processes, adaptable to wastewater with different COD concentrations.
It effectively degrades high COD wastewater under acidic to neutral conditions, improves the biodegradability of wastewater, reduces catalyst wear, enables large-scale treatment of high COD wastewater, increases the B/C ratio to 0.673849, and can degrade 45.21% of high COD wastewater within 2 hours.
Smart Images

Figure CN120989530A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment, and in particular to an Fe-based amorphous alloy that can be industrially applied to degrade high COD wastewater, its preparation method, and its application. Background Technology
[0002] With the booming development of industry, the economy has been significantly boosted; however, the resulting environmental problems have become increasingly prominent, attracting widespread social attention. Among the many environmental issues, the discharge of industrial wastewater is particularly prominent. The direct discharge of untreated industrial wastewater into the natural environment not only causes serious damage to ecosystems but also poses a potential threat to human health. Therefore, strengthening the control of industrial wastewater discharge and improving industrial wastewater treatment technologies are crucial for effectively curbing environmental pollution and achieving sustainable development, and have become a focus of global attention.
[0003] Among numerous wastewater treatment technologies, ozone oxidation has attracted considerable attention due to its powerful oxidizing ability. However, when using ozone oxidation alone to treat wastewater with high chemical oxygen demand (COD), it is often difficult to achieve ideal COD removal results. This type of high COD wastewater places enormous pressure on subsequent biological treatment processes in factories and may even affect the operational efficiency of the entire treatment system. Therefore, developing a catalyst that can effectively reduce COD and improve the biodegradability of wastewater for industrial treatment of high COD wastewater, and applying it to the large-scale treatment of industrial wastewater, is particularly urgent and significant.
[0004] Existing technologies disclose the use of iron-based amorphous alloys as catalysts for the catalytic treatment of process wastewater. However, existing iron-based amorphous alloys require the addition of H2O2 as an oxidant when treating high COD wastewater. When these two are used together to treat COD wastewater, H2O2 is easily decomposed and cannot effectively form hydroxyl radicals, resulting in a need for further improvement in the overall treatment effect. Furthermore, H2O2 poses significant risks during transportation and storage, resulting in poor safety. In addition, to achieve better treatment results, the aforementioned methods usually require stirring under acidic conditions, which is not only unsuitable for the water quality conditions of high COD industrial wastewater but also leads to catalyst wear due to stirring, affecting its effective service life. Summary of the Invention
[0005] To address the technical problems existing in the prior art, this invention provides an Fe-based amorphous alloy, its preparation method, and its application for industrial application in degrading high COD wastewater. This invention overcomes the problems of poor treatment effect of existing ozone-based wastewater treatment methods, difficulty in degrading high COD wastewater, and the burden on subsequent biochemical treatment. It also overcomes the problems of poor treatment effect, poor production safety, unsuitability for high COD wastewater conditions, and reduced catalyst lifespan associated with existing iron-based amorphous alloys combined with H2O2 for wastewater treatment. Specifically, it effectively reduces COD in high COD wastewater, improves its biodegradability, and enables large-scale treatment of high COD industrial wastewater. Furthermore, it effectively overcomes the limitations of existing ozone treatment methods.
[0006] To solve the above technical problems, the technical solution adopted by the present invention is as follows: A Fe-based amorphous alloy, with the general chemical formula Fe (based on atomic percentage), is available for industrial application in degrading high COD wastewater. a Co b Ni c Mn d Si e B f ; Where 20≤a≤80, 0≤b≤50, 0≤c≤50, 0≤d≤50, 0≤e≤20, 0≤f≤20, and a+b+c+d+e+f=100.
[0007] Preferably, the Fe-based amorphous alloy is one of the following: Fe 78 Si9B 13 Fe 40 Co 40 B 20 (FeCoNi) 80 B 20 (FeCoMn) 80 B 20 .
[0008] A method for preparing the aforementioned Fe-based amorphous alloy for industrial application in degrading high COD wastewater, according to the general chemical formula Fe... a Co b Ni c Mn d Si e B fWeigh out each elemental raw material by atomic percentage, and place each elemental raw material and titanium separately in a vacuum arc melting furnace. After evacuating and filling with protective gas, ignite the arc to melt titanium, and then ignite the arc to melt each weighed elemental raw material to obtain a master alloy ingot. Ignite the arc to melt the master alloy ingot and then perform suction casting to obtain alloy bars. Place the alloy bars in a high-vacuum single-roller spin quenching and spray casting equipment, evacuate and fill with protective gas, induction heat the alloy bars, and pressurize the melt to force it out and inject it onto a single roll to obtain an Fe-based amorphous alloy.
[0009] Preferably, the power supply for induction heating of the alloy bar in the high-vacuum single-roller spin quenching and spray casting equipment is 18-20kW, the copper wheel speed is 1600-1700r / min, and the distance between the quartz tube and the roller is 0.9-1.1mm.
[0010] Preferably, the protective gas used is argon; the gas used to pressurize the melt is also argon.
[0011] Preferably, the thickness of the Fe-based amorphous alloy is 20-35 μm.
[0012] An application of the aforementioned Fe-based amorphous alloy for industrially degrading high COD wastewater involves using the Fe-based amorphous alloy as a catalyst to catalytically degrade industrial wastewater under continuous ozone aeration conditions. The COD value of the industrial wastewater is 5600-44000 mg / L.
[0013] Furthermore, the application of the Fe-based amorphous alloy, which can be industrially applied to degrade high COD wastewater, involves adjusting the pH of the industrial wastewater to 3-9 at room temperature, continuously introducing ozone gas in the presence of the Fe-based amorphous alloy to maintain an ozone concentration of 4-44 mg / L in the industrial wastewater, thereby catalytically degrading the industrial wastewater.
[0014] Preferably, the amount of Fe-based amorphous alloy added to industrial wastewater is 0.5-1 g / L.
[0015] Furthermore, the pH of industrial wastewater can be adjusted using a hydrochloric acid solution with a concentration of 0.8-1.2 mol / L or a sodium hydroxide solution with a concentration of 0.8-1.2 mol / L. The gas generated during the catalytic degradation of industrial wastewater is treated with potassium iodide solution and sodium hydroxide solution before being discharged into the atmosphere.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The Fe-based amorphous alloy of the present invention, which can be industrially applied to degrade high COD wastewater, can be used in conjunction with ozone to catalytically degrade high COD wastewater, achieving good catalytic degradation effects in the acidic to neutral range. Simultaneously, no mechanical stirring is required during the degradation process using the Fe-based amorphous alloy and ozone, which can reduce catalyst wear while maintaining mass transfer efficiency and avoid affecting the effective service life of the catalyst. The aforementioned technical means work together synergistically to overcome the problems of poor treatment effect of existing ozone treatment of wastewater, difficulty in degrading high COD wastewater, and burden on subsequent biochemical treatment; as well as the problems of poor treatment effect, poor production safety, unsuitability for high COD wastewater quality conditions, and impact on catalyst service life of existing iron-based amorphous alloys combined with H2O2 treatment of wastewater; effectively reducing COD and improving the biodegradability of high COD wastewater, realizing large-scale treatment of high COD industrial wastewater; and effectively overcoming existing ozone treatment methods.
[0017] (2) The method for preparing Fe-based amorphous alloys for industrially applicable degradation of high COD wastewater of the present invention involves preparing FeCoNiMnSiB amorphous alloys using a vacuum magnetically controlled tungsten inert gas furnace and a high-vacuum single-roller quenching and spray casting process. In its application for the catalytic degradation of high COD wastewater, under continuous ozone aeration, catalytic degradation can reduce wastewater with a COD value of 5600 mg / L by 45.21% within 2 hours, and it can adapt to industrial wastewater with different COD concentrations. Furthermore, using the Fe-based amorphous alloy of the present invention as a catalyst, in combination with ozone, to catalytically degrade high COD wastewater without the addition of acid still exhibits satisfactory degradation performance.
[0018] (3) In the application of the Fe-based amorphous alloy for industrially degrading high COD wastewater of the present invention, the FeCoNiMnSiB amorphous alloy is used to catalytically degrade high COD wastewater with ozone. The B / C ratio can be increased from 0.61259 before ozone catalytic oxidation to 0.673849, which effectively improves the biodegradability of wastewater. Attached Figure Description
[0019] Figure 1 The figures show the XRD patterns of Fe-based amorphous alloy ribbons from Examples 1-4 and ZVI powder from Comparative Example 2; in the figures, 1 represents Fe from Example 1. 78 Si9B 13 2 is Fe from Example 2 40 Co 40 B 20 3 is (FeCoNi) from Example 3. 80 B 20 4 represents (FeCoMn) from Example 4. 80 B 205 is the ZVI powder of Comparative Example 2.
[0020] Figure 2 This is a diagram showing the degradation effect of Comparative Example 1.
[0021] Figure 3 The graph shows a comparison of the COD removal rates of Fe-based amorphous alloy strips from Examples 1-4 and ZVI powder from Comparative Example 2 on industrial wastewater under ozone aeration conditions and at pH 7; in the graph, 1 represents the Fe... 78 Si9B 13 2 is Fe from Example 2 40 Co 40 B 20 3 is (FeCoNi) from Example 3. 80 B 20 4 represents (FeCoMn) from Example 4. 80 B 20 5 is the ZVI powder of Comparative Example 2.
[0022] Figure 4 Fe as described in Example 1 78 Si9B 13 COD removal rates of amorphous alloy strips under ozone concentrations of 4 mg / L, 24 mg / L, 34 mg / L, 39 mg / L, 42 mg / L and 44 mg / L and a pH value of 7.
[0023] Figure 5 Fe as described in Example 1 78 Si9B 13 COD removal rates of amorphous alloy strips under conditions of pH 3, 5, 7, 9 and ozone concentration of 34 mg / L.
[0024] Figure 6 Fe as described in Example 2 40 Co 40 B 20 COD removal rates of amorphous alloy strips under ozone concentrations of 4 mg / L, 24 mg / L, 34 mg / L, 39 mg / L, 42 mg / L and 44 mg / L and a pH value of 7.
[0025] Figure 7 Fe as described in Example 2 40 Co 40 B 20 COD removal rates of amorphous alloy strips under conditions of pH 3, 5, 7, 9 and ozone concentration of 34 mg / L.
[0026] Figure 8 Fe as described in Example 1 78 Si9B13 COD removal efficiency of amorphous alloy strips for wastewater with different COD values.
[0027] Figure 9 Fe as described in Example 2 40 Co 40 B 20 COD removal efficiency of amorphous alloy strips for wastewater with different COD values. Detailed Implementation
[0028] To provide a clearer understanding of the technical features, objectives, and effects of this invention, specific embodiments are now described. It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0029] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, "first," "second," etc., are used to distinguish similar objects and are not used to describe a particular order or sequence. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0030] Specific embodiment one of the present invention: Provides an Fe-based amorphous alloy that can be industrially applied to degrade high COD wastewater, with the chemical formula Fe (based on atomic percentage). a Co b Ni c Mn d Si e B f Where 20≤a≤80, 0≤b≤50, 0≤c≤50, 0≤d≤50, 0≤e≤20, 0≤f≤20, and a+b+c+d+e+f=100.
[0031] This embodiment also provides the application of the Fe-based amorphous alloy that can be industrially applied to degrade high COD wastewater, using FeCoNiMnSiB amorphous alloy as a catalyst to degrade high COD wastewater in ozone.
[0032] This specific implementation method has the following beneficial effects: (1) The Fe-based amorphous alloy can effectively remove COD from industrial wastewater under continuous ozone aeration conditions. It can degrade wastewater with a COD value of 5600 mg / L by 45.21% within 2 hours and can adapt well to industrial wastewater of different concentrations.
[0033] (2) Using FeCoNiMnSiB amorphous alloy for ozone catalytic oxidation, the B / C ratio increased from 0.61259 before ozone catalytic oxidation to 0.673849, thus improving biodegradability.
[0034] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the Fe-based amorphous alloy capable of industrially degrading high COD wastewater is prepared according to the following steps: Weigh out each elemental raw material according to the atomic percentage of the general chemical formula FeaCbNcMnNnSieBf, where 20≤a≤80, 0≤b≤50, 0≤c≤50, 0≤d≤50, 0≤e≤20, 0≤f≤20, and a+b+c+d+e+f=100. Place the weighed raw materials and titanium separately in a vacuum arc melting furnace. Evacuate the furnace and fill with a protective gas. First, ignite the arc to melt the titanium, then ignite the arc to melt the weighed raw materials, obtaining a master alloy ingot. Melt the master alloy ingot using an arc and perform suction casting to obtain alloy bars. Place the alloy bars in a high-vacuum single-roller quenching and spray casting device. After evacuation, fill with a protective gas, set the copper wheel speed and start the machine. Induction heat the alloy bars, pressurize the melt, and inject it onto the single roller to obtain the FeCoNiMnSiB amorphous alloy. Other aspects are the same as in Specific Implementation Method 1.
[0035] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that the protective gas is argon. Everything else is the same as Specific Implementation Method One or Two.
[0036] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the pressurized gas is argon. Everything else is the same as Specific Implementation Methods One to Three.
[0037] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the thickness of the Fe-based amorphous alloy for industrially degrading high COD wastewater is 20-35 μm. Everything else is the same as in Specific Implementation Methods One to Four.
[0038] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that: the general chemical formula of Fe-based amorphous alloys, based on atomic percentage, is Fe. 78 Si9B 13 Fe 40 Co 40 B 20 (FeCoNi) 80 B 20 Or (FeCoMn) 80 B 20 Everything else is the same as in specific implementation methods one through five.
[0039] Specific Implementation Method Seven: This implementation method provides the application of the Fe-based amorphous alloy that can be industrially applied to degrade high COD wastewater, using the Fe-based amorphous alloy as a catalyst to degrade industrial wastewater under continuous ozone aeration conditions. The Fe-based amorphous alloy, in atomic percentage, has the general chemical formula Fe. a Co b Ni c Mn d Si e B f , where 20≤a≤80, 0≤b≤50, 0≤c≤50, 0≤d≤50, 0≤e≤20, 0≤f≤20, and a+b+c+d+e+f=100.
[0040] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Method Seven in that it uses an Fe-based amorphous alloy as a catalyst to degrade industrial wastewater under continuous ozone aeration. Specifically, it follows these steps: Adjust the pH of the industrial wastewater to 3-9, then introduce ozone gas until the ozone concentration in the wastewater reaches 4-44 mg / L. Next, add the Fe-based amorphous alloy and degrade for 2 hours under continuous ozone aeration and room temperature conditions, controlling the ozone concentration to 4-44 mg / L throughout the degradation process. The mixed gas generated during the degradation process is absorbed by potassium iodide and sodium hydroxide solutions before being discharged outdoors. Everything else is the same as in Specific Implementation Method Seven.
[0041] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Method Seven or Eight in that the amount of Fe-based amorphous alloy added is 0.5-1.0 g / L. Everything else is the same as in Specific Implementation Method Seven or Eight.
[0042] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods Seven to Nine in that it uses a hydrochloric acid solution with a concentration of 0.8-1.2 mol / L or a sodium hydroxide solution with a concentration of 0.8-1.2 mol / L to adjust the pH of the organic wastewater to 3-9. Everything else is the same as in Specific Implementation Methods Seven to Nine.
[0043] Specific Implementation Method Eleven: This implementation method differs from Specific Implementation Methods Seven to Ten in that the COD value of the industrial wastewater is 5600-44000 mg / L. Everything else is the same as in Specific Implementation Methods Seven to Ten.
[0044] Specific Implementation Method Twelve: This implementation method differs from Specific Implementation Methods Seven to Eleven in that the mass fraction of the potassium iodide solution is 2%. Everything else is the same as in Specific Implementation Methods Seven to Eleven.
[0045] Specific Implementation Method Thirteen: This implementation method differs from Specific Implementation Methods Seven to Twelve in that the mass fraction of the sodium hydroxide solution is 10%. Everything else is the same as in Specific Implementation Methods Seven to Twelve.
[0046] The present invention will be further described below with reference to some specific embodiments.
[0047] Example 1 This embodiment provides an Fe-based amorphous alloy that can be industrially applied to degrade high COD wastewater. Its chemical formula, based on atomic percentage, is Fe. a Co b Ni c Mn d Si e B f Where a=78, b=0, c=0, d=0, e=9, f=13; that is, Fe 78 Si9B 13 .
[0048] This embodiment also provides a method for preparing the Fe-based amorphous alloy, which is obtained through a vacuum magnetically controlled tungsten inert gas furnace and a high-vacuum single-roller spin quenching and spray casting system, as detailed below: According to the general chemical formula Fe a Co b Ni c Mn d Si e B f The atomic percentages of the raw materials were weighed, where a=78, b=0, c=0, d=0, e=9, f=13, to obtain the weighed raw materials; the weighed raw materials and titanium were placed separately in a vacuum arc melting furnace, and the vacuum was evacuated to 6.6×10 -3 Pa, then argon gas is introduced. First, the titanium is melted by arc for 1 minute, then the weighed raw material is melted by arc. The melting and turning are repeated more than 5 times to obtain a master alloy ingot. The master alloy ingot is then melted by arc and suction casting to obtain an alloy bar with a length of 9.0 cm and a diameter of 10 mm. The alloy bar is placed in a high-vacuum single-roller spin quenching and spray casting equipment, and the vacuum is evacuated to 6.0 × 10⁻⁶. -3 After Pa, argon gas is introduced, and the vacuum degree is 6.0 × 10⁻⁶. -3 Under the conditions of Pa, power supply heating power of 20kW, copper wheel speed of 1700r / min, and quartz tube distance from roller of 1mm, an alloy rod is induction heated, and high-purity argon gas is used to pressurize the melt and force it to be injected onto a single roller to obtain Fe. 78 Si9B 13 Amorphous alloy thin strip with a thickness of 30μm.
[0049] In the aforementioned preparation process, the total weight of the raw materials weighed was 60g. After the raw materials were cleaned, they were weighed using an analytical balance with an accuracy of 0.01%. Lightweight, volatile components or low-melting-point raw materials were placed under large pieces of high-melting-point components to reduce volatilization.
[0050] This embodiment also provides an application of using the Fe-based amorphous alloy to catalytically degrade high COD wastewater.
[0051] Example 2 This embodiment provides an Fe-based amorphous alloy that can be industrially applied to degrade high COD wastewater. Its chemical formula, based on atomic percentage, is Fe. a Co b Ni c Mn d Si e B f Where a=40, b=40, c=0, d=0, e=0, f=20; that is, Fe 40 Co 40 B 20 .
[0052] The preparation method of the Fe-based amorphous alloy in this embodiment differs from that in Example 1 in that it follows the general chemical formula Fe a Co b Ni c Mn d Si e B f The raw materials were weighed out according to atomic percentages, where a=40, b=40, c=0, d=0, e=0, and f=20; Fe was prepared. 40 Co 40 B 20 Amorphous alloy thin strip. Everything else is the same as in Example 1.
[0053] This embodiment also provides an application of using the Fe-based amorphous alloy to catalytically degrade high COD wastewater.
[0054] Example 3 This embodiment provides an Fe-based amorphous alloy that can be industrially applied to degrade high COD wastewater. Its chemical formula, based on atomic percentage, is Fe. a Co b Ni c Mn d Si e B f Where a=26.67, b=26.67, c=26.67, d=0, e=0, f=20; that is, (FeCoNi). 80 B 20 .
[0055] The preparation method of the Fe-based amorphous alloy in this embodiment differs from that in Example 1 in that it follows the general chemical formula Fe a Co b Ni c Mn d Si e B f The atomic percentages of the raw materials were weighed, where a=26.67, b=26.67, c=26.67, d=0, e=0, f=20; (FeCoNi) was prepared. 80 B 20 Amorphous alloy thin strip. Everything else is the same as in Example 1.
[0056] This embodiment also provides an application of using the Fe-based amorphous alloy to catalytically degrade high COD wastewater.
[0057] Example 4 This embodiment provides an Fe-based amorphous alloy that can be industrially applied to degrade high COD wastewater. Its chemical formula, based on atomic percentage, is Fe. a Co b Ni c Mn d Si e B f Where a=26.67, b=26.67, c=0, d=26.67, e=0, f=20; that is, (FeCoMn) 80 B 20 .
[0058] The preparation method of the Fe-based amorphous alloy in this embodiment differs from that in Example 1 in that it follows the general chemical formula Fe a Co b Ni c Mn d Si e B f The atomic percentages of the raw materials were weighed, where a=26.67, b=26.67, c=0, d=26.67, e=0, f=20; (FeCoMn) was prepared. 80 B 20 Amorphous alloy thin strip. Everything else is the same as in Example 1.
[0059] This embodiment also provides an application of using the Fe-based amorphous alloy to catalytically degrade high COD wastewater.
[0060] Comparative Example 1 In this comparative example, no catalyst was added during the degradation of high COD wastewater; ozone oxidation was performed solely through continuous ozone aeration.
[0061] Comparative Example 2 In this comparative example, zero-valent iron powder (ZVI) was used to replace Fe-based amorphous alloy as a catalyst in the degradation of high COD wastewater, and ozone catalytic oxidation was carried out under continuous ozone aeration conditions; the addition amount of zero-valent iron powder (ZVI) was controlled at 1 g / L.
[0062] Figure 1 The figures show the XRD patterns of the Fe-based amorphous alloy ribbons of Examples 1-4 and the ZVI powder of Comparative Example 2. As can be seen from the figures, the ribbons of Examples 1-4 only show amorphous diffuse scattering peaks at around 45° and no crystallization diffraction peaks, proving that the prepared ribbons are pure amorphous. The ZVI powder shows sharp crystalline phase peaks, which are consistent with the PDF card (powder diffraction standard card) of Fe.
[0063] Experimental Example 1 Using the iron-based amorphous alloy thin strips from Examples 1-4 and the ZVI powder from Comparative Example 2 as catalysts, industrial wastewater with a COD value of 10243 mg / L was catalytically degraded under an ozone concentration of 4 mg / L. Specifically: (1) Prepare 1L of industrial wastewater with a COD value of 10243mg / L using deionized water; weigh 1g of ZVI powder or Fe-based amorphous alloy thin strip with a length and width of 10mm.
[0064] (2) Place 1L of industrial wastewater solution into a 2L ozone reaction column, place 1g of weighed ZVI powder or Fe-based amorphous alloy thin strip into the reaction column, use an ozone generator with O2 as the gas source to continuously aerate the solution, and control the ozone concentration in the industrial wastewater to be 4mg / L, and degrade the industrial wastewater at room temperature of 25℃.
[0065] (3) While performing the above steps, start the stopwatch to begin timing. Take a sample after 2 hours. Filter the sample and dilute it 100 times. Take 2.5 mL of water sample into a digestion tube and add COD detection reagent in sequence. Digest at 165℃ for 10 min and air cool for 2 min. Add 2.5 mL of deionized water to the digestion tube, mix well, and place it in a cooling tank for water cooling. Detect the cooled samples with an ultraviolet spectrophotometer. Adjust the detection wavelength of the equipment to 610 nm. Multiply the measured value by 100 to get the COD value of the aqueous solution before and after ozone catalytic oxidation.
[0066] Figure 2 The figure shows the degradation effect of Comparative Example 1. As can be seen from the figure, under the condition of using ozone to oxidize industrial wastewater without adding a catalyst, the COD value of the wastewater did not decrease but increased slightly. This may be because some large organic molecules in the wastewater are converted into small organic molecules, but the overall oxidation efficiency is low and cannot effectively reduce the COD value of the wastewater, which in turn increases the load on the subsequent treatment units of the factory.
[0067] Figure 3 The graph shows a comparison of the COD removal rates of industrial wastewater by the Fe-based amorphous alloy ribbons prepared in Examples 1-4 and the ZVI powder in Comparative Example 2 under ozone aeration conditions and at pH 7; in the graph, 1 represents the Fe... 78 Si9B 13 2 is Fe from Example 2 40 Co 40 B 20 3 is (FeCoNi) from Example 3. 80 B 20 4 represents (FeCoMn) from Example 4. 80 B 20 5 represents the ZVI powder of Comparative Example 2; as shown in the figure, the Fe in Example 1... 78 Si9B 13 It exhibited optimal catalytic efficiency, removing 15.28% of the COD from wastewater within 2 hours; Example 2's Fe... 40 Co 40 B 20 The COD of the wastewater can be removed by 11.61% within 2 hours; Example 3 (FeCoNi) 80 B 20 The COD of the wastewater can be removed by 7.9% within 2 hours; Example 4 (FeCoMn) 80 B 20 Within 2 hours, the COD of the wastewater can be removed by 4.19%; compared with the ZVI powder in Comparative Example 1, the COD of the wastewater can be removed by 3.23% within 2 hours. However, the ZVI powder tends to stick to the inner wall of the reactor during the experiment, which leads to the deterioration of the catalytic effect.
[0068] Experimental Example 2 Fe prepared according to Examples 1-2 respectively 78 Si9B 13 Amorphous alloy ribbons and Fe 40 Co 40 B 20 Amorphous alloy ribbons were used as catalysts to degrade COD in industrial wastewater under different ozone concentrations and pH values. The specific steps were as follows: According to the experimental content, when investigating the effect of different ozone concentrations on COD removal rate, the ozone flow rate was adjusted to 0.5L / min, 1L / min, 1.5L / min, 2L / min, 2.5L / min, and 3L / min, corresponding to ozone concentrations of 4mg / L, 24mg / L, 34mg / L, 39mg / L, 42mg / L, and 44mg / L, respectively. When investigating the effect of pH value on COD removal rate, dilute hydrochloric acid or dilute sodium hydroxide solution was added dropwise to 1L of industrial wastewater (COD value of 7500mg / L) until the pH value was 3, 5, 7, and 9. The remaining preparation work, degradation, and detection processes were the same as in Experiment 1.
[0069] Figure 4 Fe as described in Example 1 78 Si9B 13 The COD removal rates of amorphous alloy strips under ozone concentrations of 4 mg / L, 24 mg / L, 34 mg / L, 39 mg / L, 42 mg / L, and 44 mg / L, and a pH value of 7, were as follows: COD removal rate at 4 mg / L was 17.95%; at 24 mg / L, it was 22.09%; at 34 mg / L, it was 30.95%; at 39 mg / L, it was 31.58%; at 42 mg / L, it was 32.09%; and at 44 mg / L, it was 32.19%.
[0070] Figure 5 Fe as described in Example 1 78 Si9B 13 The COD removal rates of amorphous alloy ribbons under conditions of pH 3, 5, 7, 9 and ozone concentration of 34 mg / L were measured. It was found that pH 3 showed the best removal effect, reducing the COD value of wastewater by 35.67% within 2 hours. With increasing pH, the removal efficiency gradually decreased. At pH 5, 7, and 9, the COD removal rates were 31.02%, 30.58%, and 15.51%, respectively. This result may be due to the acidic environment promoting catalyst consumption, thereby promoting the generation of free radicals and degrading pollutants. However, the removal efficiency at pH 7 was only about 5% different from that at pH 3, indicating that the catalyst in Example 1 also has good removal performance under neutral conditions. Furthermore, the B / C ratio increased from 0.61259 before ozone catalytic oxidation to 0.673849, indicating improved biodegradability.
[0071] Figure 6 Fe as described in Example 2 40 Co 40 B20 The COD removal rates of amorphous alloy ribbons under ozone concentrations of 4 mg / L, 24 mg / L, 34 mg / L, 39 mg / L, 42 mg / L, and 44 mg / L, and a pH of 7, were as follows: 14.02% at 4 mg / L; 18.23% at 24 mg / L; 25.36% at 34 mg / L; 29.29% at 39 mg / L; 33.31% at 42 mg / L; and 35.46% at 44 mg / L. The catalytic performance increased with increasing ozone concentration, and at ozone concentrations of 42 mg / L and above, it exceeded the catalytic performance of the Fe-based amorphous alloy in Example 1.
[0072] Figure 7 Fe as described in Example 2 40 Co 40 B 20 The COD removal rates of amorphous alloy ribbons were measured under pH values of 3, 5, 7, and 9, and an ozone concentration of 34 mg / L. The results showed that pH 3 exhibited the best removal efficiency, reducing the COD of wastewater by 29.79% within 2 hours. The removal efficiency gradually decreased with increasing pH. At pH values of 5, 7, and 9, the COD removal rates were 26.95%, 25.36%, and 24.58%, respectively. This result is likely due to the acidic environment promoting catalyst consumption, thereby fostering the generation of free radicals and the degradation of pollutants. However, the removal efficiency at pH 9 was only about 5% higher than that at pH 3, indicating that the catalyst also exhibits good removal performance under moderately alkaline conditions.
[0073] Experimental Example 3 Ozone catalytic oxidation experiments were conducted on industrial wastewater with different COD values using Fe-based amorphous alloy thin strips from Examples 1 and 2, respectively, as catalysts. The specific steps were as follows: According to the experimental content, raw water from different sources was selected, and a certain amount of deionized water was added to prepare water with COD values of 5600 mg / L, 7500 mg / L, 16000 mg / L, 36000 mg / L, 40000 mg / L and 44000 mg / L respectively. The rest of the preparation work and degradation and detection process were the same as those in Experiment 1.
[0074] Figure 8 Fe as described in Example 1 78 Si9B 13The COD removal efficiency of amorphous alloy strips on wastewater with different COD values was studied under the conditions of ozone concentration of 34.0 mg / L, catalyst dosage of 1 g / L, pH=7, and room temperature. The COD removal rates for production wastewater with COD values of 5600 mg / L, 7500 mg / L, 16000 mg / L, 36000 mg / L, 40000 mg / L, and 44000 mg / L were 45.21%, 31.04%, 16.86%, 10.47%, 17.63%, and 9.09%, respectively. The COD removal rate generally decreased with increasing COD value, but the removal rate increased for wastewater with a COD of 40000 mg / L, possibly because organic pollutants in this type of wastewater are more easily degraded. Furthermore, although the removal rate decreased, the COD degradation amount increased with the increase of the raw water COD value, indicating that the amorphous alloy ozone catalytic oxidation has a good degradation effect on raw water COD and can adapt well to production wastewater of different concentrations.
[0075] Figure 9 Fe as described in Example 2 40 Co 40 B 20 The COD removal efficiency of amorphous alloy strips on wastewater with different COD values was investigated under the conditions of ozone concentration of 34.0 mg / L, catalyst dosage of 1 g / L, pH=7, and room temperature. The COD removal rates for production wastewater with COD values of 5600 mg / L, 7500 mg / L, 16000 mg / L, 36000 mg / L, 40000 mg / L, and 44000 mg / L were 38.41%, 25.36%, 12.23%, 8.14%, 10.55%, and 6.67%, respectively. This trend is similar to that of Example 1.
[0076] Unless otherwise stated, all percentages used in this invention are mass percentages.
[0077] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An Fe-based amorphous alloy for industrial application in degrading high COD wastewater, characterized in that, Based on atomic percentage, the general chemical formula is Fe. a Co b Ni c Mn d Si e B f Where 20≤a≤80, 0≤b≤50, 0≤c≤50, 0≤d≤50, 0≤e≤20, 0≤f≤20, and a+b+c+d+e+f=100.
2. The Fe-based amorphous alloy for industrially degrading high COD wastewater according to claim 1, characterized in that, The Fe-based amorphous alloy is one of the following: Fe 78 Si9B 13 Fe 40 Co 40 B 20 (FeCoNi) 80 B 20 (FeCoMn) 80 B 20 .
3. A method for preparing an Fe-based amorphous alloy capable of industrially degrading high COD wastewater as described in claim 1 or 2, characterized in that, According to the general chemical formula Fe a Co b Ni c Mn d Si e B f Weigh out each elemental raw material by atomic percentage; place each elemental raw material and titanium separately in a vacuum arc melting furnace, evacuate and fill with protective gas, then ignite the arc to melt titanium, and then ignite the arc to melt each elemental raw material to obtain a master alloy ingot; ignite the arc to melt the master alloy ingot and then perform suction casting to obtain alloy bars; place the alloy bars in a high vacuum single-roller quenching and spray casting equipment, evacuate and fill with protective gas, induction heat the alloy bars, and pressurize the melt to force it out and inject it onto a single roll to obtain an Fe-based amorphous alloy.
4. The method for preparing Fe-based amorphous alloys for industrially applied degradation of high COD wastewater according to claim 3, characterized in that, The power supply for induction heating of alloy bars in high-vacuum single-roller spin quenching and spray casting equipment is 18-20kW, the copper wheel speed is 1600-1700r / min, and the distance between the quartz tube and the roller is 0.9-1.1mm.
5. The method for preparing Fe-based amorphous alloys for industrially applied degradation of high COD wastewater according to claim 3, characterized in that, The protective gas used is argon; Argon is the gas used to pressurize the melt.
6. The method for preparing Fe-based amorphous alloys for industrially applied degradation of high COD wastewater according to claim 3, characterized in that, The thickness of the Fe-based amorphous alloy is 20-35 μm.
7. The application of an Fe-based amorphous alloy as described in claim 1 or 2, capable of industrially degrading high COD wastewater, characterized in that... Using the aforementioned Fe-based amorphous alloy as a catalyst, industrial wastewater is catalytically degraded under continuous ozone aeration conditions; The COD value of the industrial wastewater is 5600-44000 mg / L.
8. The application of the Fe-based amorphous alloy for industrially degrading high COD wastewater according to claim 7, characterized in that, At room temperature, the pH of the industrial wastewater is adjusted to 3-9. In the presence of Fe-based amorphous alloy, ozone gas is continuously introduced to maintain the ozone concentration in the industrial wastewater at 4-44 mg / L, thereby catalytically degrading the industrial wastewater.
9. The application of the Fe-based amorphous alloy for industrially degrading high COD wastewater according to claim 7, characterized in that, The addition amount of Fe-based amorphous alloy to industrial wastewater is 0.5-1 g / L.
10. The application of the Fe-based amorphous alloy for industrially degrading high COD wastewater according to claim 8, characterized in that, The pH of industrial wastewater is adjusted using a hydrochloric acid solution with a concentration of 0.8-1.2 mol / L or a sodium hydroxide solution with a concentration of 0.8-1.2 mol / L. The gases generated during the catalytic degradation of industrial wastewater are treated with potassium iodide solution and sodium hydroxide solution before being discharged into the atmosphere.